2020
DOI: 10.1101/2020.10.20.20203927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of a COPD-Associated NPNT Functional Splicing Genetic Variant in Human Lung Tissue via Long-Read Sequencing

Abstract: Chronic obstructive pulmonary disease (COPD) is a leading cause of death worldwide. Genome-wide association studies (GWAS) have identified over 80 loci that are associated with COPD and emphysema, however for most of these loci the causal variant and gene are unknown. Here, we utilize lung splice quantitative trait loci (sQTL) data from the Genotype-Tissue Expression project (GTEx) and short read sequencing data from the Lung Tissue Research Consortium (LTRC) to characterize a locus in nephronectin (NPNT) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Thus, we evaluated whether the cis-pQTL influenced either total RNA expression level or a specific isoform level of NPNT. Given that the lung is a primary target organ in the context of COVID-19 severity, NPNT is highly expressed in the lung, NPNT splice isoforms have previously been implicated as a risk factor for COPD and other lung outcomes 38,39,40 , and SNPs influencing a specific isoform level would be a splice QTLs (sQTLs), we performed colocalization analysis of the cis-pQTL with eQTLs and sQTLs for NPNT in lung tissue from GTEx 41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we evaluated whether the cis-pQTL influenced either total RNA expression level or a specific isoform level of NPNT. Given that the lung is a primary target organ in the context of COVID-19 severity, NPNT is highly expressed in the lung, NPNT splice isoforms have previously been implicated as a risk factor for COPD and other lung outcomes 38,39,40 , and SNPs influencing a specific isoform level would be a splice QTLs (sQTLs), we performed colocalization analysis of the cis-pQTL with eQTLs and sQTLs for NPNT in lung tissue from GTEx 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the lead cis-pQTL from the deCODE study, i.e., rs34712979, was also identified by the FENLAND study 27 and has been reported to create a cryptic splice acceptor site, which inserts a three-nucleotide sequence coding a serine residue at the 5'-splice site of exon 2, resulting in perturbations of the alpha-helix motif 38 . Further, this lead cis-pQTL (rs34712979) and another cis-pQTL (rs78213340) from the AGES Reykjavik study-that was not in high LD with rs34712979 (r 2 = 0.234)-were both associated with the same exon-skipping splicing in lung in GTEx (Supplementary Table 14).…”
Section: Colocalization Analyses Investigating Whether Cis-pqtl For N...mentioning
confidence: 97%
“…A recent preprint indicates that a splice variant of NPNT includes an additional serine residue in the splice site, and is associated with COPD. The serine residue is predicted to be located between the signal peptide and the first EGF-like repeat [ 57 ]. The structure and function of this newly discovered variant of NPNT is still to be resolved.…”
Section: Expression and Functional Roles Of Npntmentioning
confidence: 99%
“…Other studies have also demonstrated that Npnt plays a potential role in diseases such as chronic obstructive pulmonary disease (COPD) (Saferali et al, 2020), diabetic glomerulosclerosis (Nakatani et al, 2012), Fraser syndrome (Kiyozumi et al, 2012), and in various cancers (Magnussen et al, 2021). Despite the pleiotropic functions of Npnt in development and disease, its expression and function have not yet been described in the cornea.…”
Section: Introductionmentioning
confidence: 99%